Q: What is the first derivative of 3x- 4sq root 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Take the derivative of (3x+1)1/2First use the power rule on the entire function, then multiply it by the derivative of the inside:(1/2)(3x-1)-1/2(3) = (3/2)(3x-1)-1/2which can also be written as3/(2sqrt(3x-1))(sqrt stands for square root)

f'(x)=-3the derivative of e is zero because its a constant. Derivative of -3x is -3. Bring the exponent of x down in front of the -3 and subtract the original exponent by 1. Ex. -3(1...which is the first exponent of the x)x^0(n-1 or 1-1=0)all this is -3(1)x^0x^0 is 1 so the derivative of -3x is -3

√(24x)4/√(3x) = [242x2√(3x)]/3x = 8(24)x√(3x) = 192x√(3x)

d/dx 2x2+3x+7=4x+3

2 root 3x

Related questions

The derivate of 3x is 3; the derivative of -1 is 0. So, the derivative of 3x-1 is simply 3.The derivate of 3x is 3; the derivative of -1 is 0. So, the derivative of 3x-1 is simply 3.The derivate of 3x is 3; the derivative of -1 is 0. So, the derivative of 3x-1 is simply 3.The derivate of 3x is 3; the derivative of -1 is 0. So, the derivative of 3x-1 is simply 3.

If y = 3x +- 1, the derivative with respect to x is y' = 3.

Take the derivative of (3x+1)1/2First use the power rule on the entire function, then multiply it by the derivative of the inside:(1/2)(3x-1)-1/2(3) = (3/2)(3x-1)-1/2which can also be written as3/(2sqrt(3x-1))(sqrt stands for square root)

In this case, you'll need to apply the chain rule, first taking the derivative of the tan function, and multiplying by the derivative of 3x: y = tan(3x) ∴ dy/dx = 3sec2(3x)

The derivative of y = sin(3x + 5) is 3cos(3x + 5) but only if x is measured in radians.

3e3x

3sec2(3x)

4

the derivative of 3x is 3 the derivative of x cubed is 3 times x squared

f'(x)=-3the derivative of e is zero because its a constant. Derivative of -3x is -3. Bring the exponent of x down in front of the -3 and subtract the original exponent by 1. Ex. -3(1...which is the first exponent of the x)x^0(n-1 or 1-1=0)all this is -3(1)x^0x^0 is 1 so the derivative of -3x is -3

9x2

√(24x)4/√(3x) = [242x2√(3x)]/3x = 8(24)x√(3x) = 192x√(3x)